The Lithuanian American Cultural Press in English (1950-1990) in the Aspect of the Dissemination of the Lithuanian Identity - Budriūnienė, Jolanta (Knygotyra, 2020)
The article examines the publication of the cultural press in English by the Lithuanian community in the United States (1950-1990), focusing on the analysis of the need for such a press and its intended addressee. The article is based on the analysis of the content of the mentioned publishing production, works dedicated to the history of the Lithuanian diaspora of this period. By reviewing the research of the Lithuanian press in the USA in the 2nd half of the 20th century, it has to be noticed that this field of research has not yet sufficiently exhausted, although the general research of the Lithuanian diaspora is really abundant. However, they mainly focus on the historical, sociological, literary, linguistic description of the problems of the diaspora and migration. Research on publishing of the Lithuanian diaspora in the Lithuanian language in the early period (end of the 19th century – first half of the 20th century) has been carried out and published in the scientific works of Ass. Prof. Dr. Bronius Raguotis, Prof. Dr. Remigijus Misiūnas. At the end of World War II, the tendencies of the press of other languages of Lithuanians, who chose a forced exile, in the conditions of DP (DP – displaced people) were also presented by Prof. Dr. R. Misiūnas. A detailed analysis of the Lithuanian cultural press published in the German DP camps was presented in the monograph by Prof. Dr. Dalia Kuizinienė. Meanwhile, the press of other languages of Lithuanian communities in both the United States and other foreign countries had not yet reached the attention of researchers. In the presented study, Pierre Bourdieu, a theorist of literary sociology, uses the insights of literature as an important social factor covering all elements of cultural practice and allows for a systematic interpretation of their interrelationships; the approaches of the communication strategy of the Lithuanian American cultural press in English are analyzed. The article presents the main content of the cultural press and the social and cultural environment that formed the background of its creation, as well as the efforts of the creators of the cultural press and the ideological attitudes of the intellectuals and ideological leaders of the community that determined them. The article concludes that the main addressee of this press – members of the US communities, while the main focus of the content is the representation of symbols of the Lithuanian national identity.